Penerapan Metode Hayami dalam Analisis Nilai Tambah Pengolahan Ikan Bandeng Menjadi Amplang - Hasiani, Yarna; Maulana Ash'ari, Fuzi; Suslinawati; Pandi (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2024)
Fish is a perishable food so special handling is required to maintain its quality. Post-harvest handling of agricultural and fishery products is an activity downstream agribusiness subsystem. Post-harvest handling has an impact on selling prices. This Research aims to analyze the added value of the processing of milkfish (Chanos chanos) into “Amplang” (Indonesian traditional snack) in Rampa Manunggul Village, Sampanahan Subdistrict, Kotabaru Regency, South Kalimantan Province. Data analysis in this research used the Hayami method. Data was collected using the case study method on Amplang processing business